Faktor-faktor yang mempengaruhi tingkat pengangguran terdidik di Provinsi Jambi - Rosalina Rosalina; Purwaka Hari Prihanto; Erni Achmad (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2018)
The study aims to analyze the influence of education levels, economic growth, employment opportunities and wages on the level of educated unemployment in Jambi Province. The data used is time series secondary data from 2001-2016. Data is sourced from the Central Bureau of Statistics of Jambi Province. Data were analyzed descriptively and multiple regression models. The results showed that simultaneously the level of education, economic growth, the level of employment and wages had a significant influence on the level of educated unemployment in Jambi Province. Partially the level of education and the level of employment have a significant effect while economic growth and wages do not affect the level of educated unemployment in Jambi Province.